2019
DOI: 10.1039/c9cc04132j
|View full text |Cite
|
Sign up to set email alerts
|

A NIR-II light responsive hydrogel based on 2D engineered tungsten nitride nanosheets for multimode chemo/photothermal therapy

Abstract: A hydrogel drug cargo based on 2D tungsten nitride nanosheets was fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Compared to the near-infrared-I (NIR-I, 650-950 nm), NIR-II wavelength possesses lower photon scattering, tissue absorption, as well as deeper photon penetration, leading to higher light-penetration efficacy and better spatial resolution. [8] Regulation of angiogenesis is a great challenge for effective anticancer therapy. Generally, anti-angiogenic therapies are focused on inhibition of inducers involved in pro-angiogenic communication pathways.…”
mentioning
confidence: 99%
“…Compared to the near-infrared-I (NIR-I, 650-950 nm), NIR-II wavelength possesses lower photon scattering, tissue absorption, as well as deeper photon penetration, leading to higher light-penetration efficacy and better spatial resolution. [8] Regulation of angiogenesis is a great challenge for effective anticancer therapy. Generally, anti-angiogenic therapies are focused on inhibition of inducers involved in pro-angiogenic communication pathways.…”
mentioning
confidence: 99%
“…SAPNS represents an advancement in biological materials, due to its ability to absorb moisture and insoluble 3-dimensional polymer hydrogels. Currently, sNAG hydrogels have been used in clinical practice as biological scaffolds [20,21]. Recent studies have reported that hydrogels can be encapsulated mesoporous silicon coated gold nanoshells as the only drug transporter [22], achieving outstanding clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 5) There have been sparse in vitro data on the effects of 2D tungsten compounds in immune cells although it has been found that human skin fibroblasts preferentially adhere to tungsten compared to silicon oxide in a 2D tungstensilicon oxide composite [222] and that no histological abnormalities were reported in mouse heart, liver, spleen, lungs or kidney after 16 days of 2D tungsten nitride nanosheets. [223] Another paper also reported no histological organ abnormalities after 30 days although high levels of 2D WS2-PEG nanosheets were found in the liver and spleen. [153] We included this element in our review as it is an emerging 2D nanomaterial.…”
Section: Tungsten Nanomaterialsmentioning
confidence: 97%